2018
DOI: 10.3390/ijms19092752
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid in Colon Cancer: From the Basic to the Clinical Applications

Abstract: Given the safety and potential benefits of intravenous ascorbic acid (AA) administration in cancer patients, there is merit in further exploring this therapeutic concept. In this review, we discuss the potential benefits of intravenous AA administration on colorectal cancer and we specifically focus on its effect on glycolysis in mutant and wild type RAS. We perform a PubMed and Ovid MEDLINE search using ascorbic acid, intravenous vitamin C, KRAS mutation, BRAF mutation and colorectal cancer (CRC) as keywords.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…Furthermore, when applying vitamin C to duodenal explants derived from patients suffering from coeliac disease due to a hypersensitivity reaction to wheat gliadin and similar proteins from rye and barley [57], a decreased secretion of pro-inflammatory mediators in response to gluten could be assessed [58]. In addition, in a small study cohort, intravenous high dose vitamin C application was found to be beneficial as an adjunct treatment option of colorectal cancer [59]. Hence, vitamin C has been shown to exhibit potent immunomodulatory activity in the course of distinct gastrointestinal inflammatory morbidities.…”
Section: Immunomodulatory Properties Of Vitamin Cmentioning
confidence: 99%
“…Furthermore, when applying vitamin C to duodenal explants derived from patients suffering from coeliac disease due to a hypersensitivity reaction to wheat gliadin and similar proteins from rye and barley [57], a decreased secretion of pro-inflammatory mediators in response to gluten could be assessed [58]. In addition, in a small study cohort, intravenous high dose vitamin C application was found to be beneficial as an adjunct treatment option of colorectal cancer [59]. Hence, vitamin C has been shown to exhibit potent immunomodulatory activity in the course of distinct gastrointestinal inflammatory morbidities.…”
Section: Immunomodulatory Properties Of Vitamin Cmentioning
confidence: 99%
“…The control of L-AA absorption from the intestine is very strict, but recent pharmacokinetic data suggest that intravenous L-AA can bypass this tight control leading to higher plasma levels (12,13). As a result, L-AA has been redefined as a potential anticancer drug in recent years (4,6,14).…”
Section: Introductionmentioning
confidence: 99%
“…The risk of adverse effects and intoxication upon high-dose ingestion may be considered negligible in subjects with intact renal function, given that vitamin C is water-soluble and concentrations exceeding the daily demands will be excreted via the kidneys 80 .Together, ascorbate application can be considered as safe and has been pharmaceutically approved for the treatment of gastrointestinal morbidities in humans 33,60,81 . Interestingly, several inflammatory morbidities within the gastrointestinal tract have been shown to be associated with reduced ascorbate plasma concentrations 82,83 .…”
Section: Discussionmentioning
confidence: 99%